Sound financial institutional frameworks, unsound outcomes : the case of Jamaica - Thomas, Desmond (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Addresses the conundrum of unstatifactory outcomes with respect to stabilization and growth depite the existence of an institutionsl framework that appears to be relatively sound for the most part.